Skeletal muscle interstitial O2 pressures: bridging the gap between the capillary and myocyte. (10th October 2018) - Hirai, Daniel M.; Colburn, Trenton D.; Craig, Jesse C.; Hotta, Kazuki; Kano, Yutaka; Musch, Timothy I.; Poole, David C.
Abstract: The oxygen transport pathway from air to mitochondria involves a series of transfer steps within closely integrated systems (pulmonary, cardiovascular, and tissue metabolic). Small and finite O2 stores in most mammalian species require exquisitely controlled changes in O2 flux rates to support elevated ATP turnover. This is especially true for the contracting skeletal muscle where O2 requirements may increase two orders of magnitude above rest. This brief review focuses on the mechanistic bases for increased microvascular blood‐myocyte O2 flux (V̇O2 ) from rest to contractions. Fick's law dictates that V̇O2 elevations driven by muscle contractions are produced by commensurate changes in driving force (ie, O2 pressure gradients; ΔPO2 ) and/or effective diffusing capacity (DO2 ). While previous evidence indicates that increased DO2 helps modulate contracting muscle O2 flux, up until recently the role of the dynamic ΔPO2 across the capillary wall was unknown. Recent phosphorescence quenching investigations of both microvascular and novel interstitial PO2 kinetics in health have resolved an important step in the O2 cascade between the capillary and myocyte. Specifically, the significant transmural ΔPO2 at rest was sustained (but not increased) during submaximal contractions. This supports the contention that the blood‐myocyte interface provides a substantial effective resistance to O2 diffusion and underscores that modulations in erythrocyte hemodynamics and distribution (DO2 ) are crucial to preserve the driving force for O2 flux across the capillary wall (ΔPO2 ) during contractions. Investigation of the O2 transport pathway close to muscle mitochondria is key to identifying disease mechanisms and develop therapeutic approaches to ameliorate dysfunction and exercise intolerance.